2022
DOI: 10.1111/lam.13828
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the oral and faecal microbiota associated with atopic dermatitis in dogs selected from a purebred Shiba Inu colony

Abstract: Atopic dermatitis (AD) is a chronic and relapsing multifactorial inflammatory skin disease that also affects dogs. The oral and gut microbiota are associated with many disorders, including allergy. Few studies have addressed the oral and gut microbiota in dogs, although the skin microbiota has been studied relatively well in these animals. Here, we studied the AD‐associated oral and gut microbiota in 16 healthy and 9 AD dogs from a purebred Shiba Inu colony. We found that the diversity of the oral microbiota w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 56 publications
2
16
0
Order By: Relevance
“…Multiple studies have demonstrated that both dogs and humans with AD suffer from cutaneous dysbiosis. 1,[27][28][29][30][31][32][33][34] Whether the dysbiosis is a cause or a consequence of the atopic state remains unclear. However, a recent birth cohort study sampling 109 puppies and 34 parent dogs from Switzerland showed that although the development of skin microbiota (bacterial and fungal) is influenced by both age and environmental factors (e.g.…”
Section: Updates On Cutaneous Microbiomementioning
confidence: 99%
“…Multiple studies have demonstrated that both dogs and humans with AD suffer from cutaneous dysbiosis. 1,[27][28][29][30][31][32][33][34] Whether the dysbiosis is a cause or a consequence of the atopic state remains unclear. However, a recent birth cohort study sampling 109 puppies and 34 parent dogs from Switzerland showed that although the development of skin microbiota (bacterial and fungal) is influenced by both age and environmental factors (e.g.…”
Section: Updates On Cutaneous Microbiomementioning
confidence: 99%
“…Some allergy-associated gut microbial signatures have been identified in humans, either preceding the disease [49,50] or after the onset of the disease [51][52][53]. Information on how and which gut microbes are associated with allergy or atopy (AD) in dogs is scarce and from small samples [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Concurrently, allergy prevalence among dogs seems to be increasing [ 24 ]. The differences in the gut microbiota between atopic and healthy dogs are not widely studied [ 25 , 26 ], in particular considering the concurrent effect of diet. Similarly to humans [ 27 ], diet plays a dominant role in affecting gut microbial compositions also in pet dogs [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, altered microbiome pro les are observed in dogs with chronic or acute gastrointestinal diseases [2][3][4] , and symptoms are improved with treatments targeting the gut microbiome, such as probiotics or fecal microbiota transplant [5][6][7][8] . Dogs with chronic diseases such as obesity [9][10][11] , diabetes mellitus 12 , atopic dermatitis 13,14 , poor cognition 15 , and behavioral issues are also found to have different gut microbiome pro les from their healthy counterparts 16,17 , although specialized diets prescribed for these conditions may partially explain such differences. Since diet has a direct impact on the gut microbiome and is a modi able factor that dogs are exposed to on a daily basis, a large amount of effort has been made to identify the relationships between diet and the gut microbiome 1,18 .…”
Section: Introductionmentioning
confidence: 99%